Effect of STEM Designed Activities on Academic Achievement of 7th Grade Elementary School Students in Force and Energy Unit - Sayılgan, E.; Akkuş, Adem; Yıldırım, Bekir (International Council of Associations for Science Education (ICASE), 2022)
The purpose of this study was to examine the effect of STEM designed activities on academic achievement of 7th grade elementary school students in work and energy unit. For that purpose, four STEM activities were chosen to be implemented in the work and energy unit. Semi-experimental research design was utilized for the research. Two different classrooms were chosen randomly as control and STEM group. 19 students were in the control group and 21 students in the STEM group. Both classrooms were instructed by the same teacher with the same instruction time. The only difference between the groups was the STEM integrated activities. Initial analyzes revealed that there was no statistically significant difference between the groups in terms of academic knowledge level prior the study. After implementing the STEM activities for the STEM group, statistical analyzes revealed that there was a statistical positive difference in favor of the STEM group. After a month, posttest was administered to STEM group in order to determine the retention level of the students. Analyzes revealed that there was no statistically significant difference between control group and STEM group.Analyzes revealed that there was no statistically significant difference between boys and girls in STEM group. It was concluded by the study that in the long-term STEM integrated curricula would benefit elementary science students and would decrease the gender gap in STEM related areas. © 2022 Journal of Open Humanities Data. All rights reserved.
Keywords: Elementary science; gender difference; STEM; STEM activities; students